Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Parinduri, Ahmad Buchari; Andri Zainal; La Hanu; Ramdhansyah; Tuti Sriwedari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In this research, there were problems that showed a low level of learning activity and also in the initial ability test of students showed that the learning outcomes of the cognitive domain of students on the material of the adjusting journal were still low. The purpose of this research was to determine the increase in students' accounting activities and learning outcomes in class XII IPS 2 at SMA Swasta Dharmawangsa Medan through the application of the Two Stay Two Stray type cooperative learning model on the material of the trading company's adjustment journal. This type of research is Classroom Action Research (PTK) which is carried out in two cycles. The subjects in this study were 27 students of class XII IPS 2. The instruments in this study consisted of knowledge tests and activity observation sheets. The results of the observation of student activity in cycle I there were 9 students (34%) who fell into the active and very active categories. In cycle II students who were included in the active and very active categories increased to 27 students (100%) and had met the success indicator >85%. And from the results of data analysis, the first cycle knowledge test was obtained with an average value of 62.2 with 15 students (56%) and an increase in the second cycle knowledge test with an average value of 84.1 with 26 students (96%) and has met the success indicator >85%. Based on these data, the indicators of this study have been met. So, it can be concluded that the application of the Two Stay Two Stray type cooperative learning model can improve student learning activities and outcomes at SMA Swasta Dharmawangsa Medan.